(untitled) (Journal of Engineering, 2022)
The slurry infiltrated fiber concrete (SIFCON) is nowadays considered a special type of high fiber content concrete; it is high strength and high performance material. This paper investigates the effect of spread steel fiber into the slurry mortar on some properties of SIFCON. According to fiber distribution, two sets were used in this investigation. The first set consisted of randomly distributing fibers inside the slurry. The second set was by placing the fibers in an orderly manner inside the slurry. Crimped steel fibers with an aspect ratio of (60) were used. Two different volume fractions percentage of (7% and 9%) by volume of mold were used in both sets for this study. Also, a w/c ratio of (0.35) and superplasticizer of (1%) by weight of cement was used to ensure the penetration of the slurry inside the fibers. The compressive and flexural strength were conducted on standard cubes (10*10*10) cm and prisms of (40*7*7) cm respectively to find the effect of how the steel fibers were distributed. The results showed that distributing the fibers randomly gave better results than the ordered distribution. The increment percentage in compressive strength and flexural strength were (1.5%, 6.9%, 23%, and 6.5%), respectively, for both sets and both fiber volume fractions (7% and 9%).